Familial Narcolepsy in Dogo Argentino Dogs Is Caused by a Tandem Duplication Mutation in HCRTR2 - Alejandra Mondino; Michael W. Vandewege; Rody Artigas; Luis Delucchi; Karen M. Hermida; Camila E. Yanez; Jonah N. Cullen; Steven G. Friedenberg; Kathryn M. Meurs; Joshua A. Stern; Natasha J. Olby (Journal of Veterinary Internal Medicine)
ABSTRACT Background Familial narcolepsy in dogs has been associated with mutations in the HCRTR2 gene in Labrador retrievers, dachshunds, and Doberman pinschers, with the causal mutation differing between breeds. Objective To characterize the genetic mutation responsible for familial narcolepsy in Dogo Argentino dogs. Animals Ten Dogo Argentino dogs, three narcoleptic and seven clinically normal, of which four were related and three were unrelated to the narcoleptic dogs. Methods Case control prospective study. DNA was extracted from blood samples of all dogs. Whole‐genome sequencing was performed on two affected dogs, and variants were identified using bioinformatic pipelines, with comparisons made to a database of 2766 dogs. Structural variants were validated through PCR and Sanger sequencing. Results A novel tandem duplication in the HCRTR2 gene was identified. All three affected dogs and the clinically normal parents of one affected dog had this duplication, suggesting an autosomal recessive pattern of inheritance. This duplication was absent in the 2766 dogs in the database, emphasizing its potential relevance in the Dogo Argentino breed. Conclusions and Clinical Importance This discovery emphasizes the critical role of the HCRTR2 gene in narcolepsy in dogs, and the diversity of mutations that can lead to this condition. Further genetic testing in this breed is warranted to identify carriers and prevent the further spread of this condition.